THE ADAPTABILITY TO CULTURE CONDITION OF SOME COMMON CORAL GENERA - Thuy, Nguyen Thi Thanh (Vietnam Journal of Marine Science and Technology, 2014)
Four common coral genera in culture conditions are Symphyllia, Plerogyra, Euphyllia and Goniopora. They are long/large polyp stony corals, sexual and asexual reproduction. Except Symphyllia, the three genera are aggressive towards the other marine aquarium invertebrates. All of the four coral genera have 2 feeding modes: autotrophic mode through photosynthesis of symbiotic zooxanthellea and heterotrophic mode including 3 ways: predatory prey capture by the polyps; sedimentary filter feeding using mucus nets; consume dissolved organic matter through cell membranes. Both Symphyllia and Plerogyra easily adapt to culture conditions. However, tissue of Symphyllia is subjected to tearing if not handled appropriately.Euphyllia rather adapt to culture conditions but somewhat prone to brown jelly type infections and direct light from metal halide. It is not easy adapting to culture conditions for Goniopora, easily infected by brown jelly, bleaching and impact of high water flow. In culture conditions, the four coral genera are fed on processed seafood with suitable sizes, require light intensity 5,500 - 20,000°K; pH 8.1 -8.4; salinity 33 - 34‰; water flow 10 - 30%h-; calcium 400 - 450ppm; alkalinity 150 - 250ppm CaCO3; magnesium 1,200 - 1,350ppm; Strontium 8 - 10ppm phosphate 0ppm.